2015
DOI: 10.1097/mbp.0000000000000142
|View full text |Cite
|
Sign up to set email alerts
|

Should blood pressure be measured with the cuff on a bare arm?

Abstract: We could not find differences in MAP, SBP, and DBP between the bare and clothed arms, but intraindividual variation of SBP between the three conditions is not negligible. Despite this caveat, these data suggest that in an outpatient clinic, BP can be measured reliably with one layer of clothing underneath the cuff. This is timesaving and more comfortable for patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 9 publications
(17 reference statements)
1
9
0
Order By: Relevance
“…No statistical differences were determined between SBP/DBP measurements taken over the sleeve and below a rolled-up sleeve. These data are supported by the findings of previous studies 7,9-12…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…No statistical differences were determined between SBP/DBP measurements taken over the sleeve and below a rolled-up sleeve. These data are supported by the findings of previous studies 7,9-12…”
Section: Discussionsupporting
confidence: 92%
“…Thien et al12 measured the normotensive/hypertensive male/female patients’ blood pressure over the sleeve and on the bare arm using an oscillometric device. They did not find differences in blood pressure between over the sleeve and bare arms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have found that readings taken over the sleeve of a shirt, blouse, or light sweater are not statistically different from those taken on bare arms or with rolled-up sleeves (e.g. Ma et al, 2008; Thien et al, 2015 ). In an outpatient clinic, blood pressure can be measured reliably with one layer of clothing underneath the cuff.…”
Section: Measures: Space Posture and Multiple Bodiesmentioning
confidence: 96%
“…In an outpatient clinic, blood pressure can be measured reliably with one layer of clothing underneath the cuff. This saves time and is supposed to be more comfortable for patients (Thien et al, 2015). It may be preferable because of hygiene concerns, patient privacy and religious beliefs (Rukiye et al, 2010).…”
Section: Measures: Space Posture and Multiple Bodiesmentioning
confidence: 99%